Nahda – The Socio-Philosophical Essence Of The Arab Renaissance - Muxammadjon T. Parpiyev (Periodica Journal, 2025)
This article explores the socio-philosophical foundations of the Nahda, or Arab Renaissance, a pivotal intellectual and cultural awakening in the Arab world during the 19th and early 20th centuries. The study analyzes how Arab thinkers sought to reconcile traditional Islamic values with the ideals of modernity, inspired by both internal philosophical traditions and external influences such as the European Enlightenment. It highlights the revival of classical Arab-Islamic thought, the impact of colonial encounters, and the intellectual transformation that led to cultural renewal. Special attention is given to the contributions of key reformist scholars who blended heritage with progress to shape a modern Arab identity. The Nahda is presented not only as a response to historical stagnation but also as a dynamic movement of identity reconstruction, modernization, and resistance to cultural domination
Keywords: Nahda; Arab Renaissance; modernity; Islamic philosophy